The Role of Reverend Canon John Rujoki in the Revival Movement in Kanoni Arcdeaconry - Asaph Amanya (Uganda Christian University, 2024)
This study examines the life and ministry of Rev. Can. John Rujoki, focusing on his methods, achievements, and challenges in the revival movement in Ankole, Uganda. Using a qualitative research approach, the study utilizes historical analysis and content analysis of primary sources to assess Rujoki's methods in evangelism, community engagement, and spiritual growth. The achievements of Rujoki are evaluated through a comparative analysis of the impact of his ministry on the Church and community in Ankole, before and after his leadership. Additionally, the study investigates the challenges faced by Rujoki, including barriers to Church growth, cultural and societal resistance, and theological complexities. Findings reveal that Rev. Can. John Rujoki employed various methods in the revival movement, including personal evangelism, the door-to-door movement, lifestyle evangelism, and a focus on prayer and Bible study. These methods were characterized by a deep commitment to sharing the gospel, building relationships, and fostering spiritual growth among believers, demonstrating his holistic approach to ministry. His achievements in the revival movement are multifaceted, encompassing spiritual renewal and growth, community transformation, Church planting and development, leadership and mentorship, unity and collaboration, and a lasting legacy of faith. Despite facing significant challenges, including difficulties in Church expansion, impact of modern trends like the prosperity gospel, challenges posed by Pentecostalism, sustainable Church growth, and issues of relevance and identity faced by African Independent Churches, Rev. Can. John Rujoki's resilience and commitment to spreading the gospel were evident in his lasting impact on Ankole. The study concludes that Rev. Can. John Rujoki's methods were instrumental in achieving significant milestones in Ankole, and recommends that Churches should continue emphasizing these methods and the values he embodied to sustain the impact of the revival movement.
Undergraduate Research
Keywords: John Rujoki; Revival Movement; Kanoni Arcdeaconry